Impactos da urbanização sobre os parâmetros climáticos, em duas áres de Fortaleza, Ceará - Petalas, Kety Vasconcelos (2000)
Urban expansion has been one of the main responsible for changes in the environment, affecting not only the physical environment but also the biotic and anthropic. The manifestations provoked in the characteristics of the soil are manifested in the atmosphere, in the hydrological cycle and in the life of the living beings, being able to limit the human development. This study seeks to verify the effect of urbanization on climatic parameters within the Urban Coverage Layer in two areas of the city of Fortaleza, state of Ceará, Brazil. It also seeks to describe the impacts caused by urbanization as a whole, in order to explain how man interferes in his environment. Preceding the identification of climate change in Fortaleza, its urban evolution is briefly described and climatically characterized. In the design of the study, hypotheses are presented based on theoretical knowledge, with the main objective of: verifying the effect of urbanization on the climatic parameters of the FUNCEME and INEMET-UFC stations. For this, the Signal Test (Cox-Stuart, non-parametric) and the technique of visual observation of the area around each station are used. In the analysis of the results, it appears that FUNCEME (more urbanized area) presents a greater number of alterations than INEMET-UFC (less urbanized area), confirming the hypotheses raised. However, it cannot be said that such changes are occurring exclusively due to urbanization.